2017
DOI: 10.1016/j.celrep.2016.12.065
|View full text |Cite
|
Sign up to set email alerts
|

Testis-Specific Histone Variant H3t Gene Is Essential for Entry into Spermatogenesis

Abstract: Cellular differentiation is associated with dynamic chromatin remodeling in establishing a cell-type-specific epigenomic landscape. Here, we find that mouse testis-specific and replication-dependent histone H3 variant H3t is essential for very early stages of spermatogenesis. H3t gene deficiency leads to azoospermia because of the loss of haploid germ cells. When differentiating spermatogonia emerge in normal spermatogenesis, H3t appears and replaces the canonical H3 proteins. Structural and biochemical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 24 publications
(33 reference statements)
1
57
0
1
Order By: Relevance
“…This idea is supported by structural data showing that histone variants alter nucleosome properties (3,8–18). Some histone variants evolved only amongst specific taxa, such as testicular H3 in mammals (19,20), sperm specific variants in plants (21), H2A.W in land plants (22), macroH2A in metazoans (23), H2A.L and H2A.B in mammals (24) and sperm specific variants H2A.Q and H2A.R in mammals (25). …”
Section: Introductionmentioning
confidence: 99%
“…This idea is supported by structural data showing that histone variants alter nucleosome properties (3,8–18). Some histone variants evolved only amongst specific taxa, such as testicular H3 in mammals (19,20), sperm specific variants in plants (21), H2A.W in land plants (22), macroH2A in metazoans (23), H2A.L and H2A.B in mammals (24) and sperm specific variants H2A.Q and H2A.R in mammals (25). …”
Section: Introductionmentioning
confidence: 99%
“…H3t is synthesized in spermatogonia and remains detectable in spermatocytes and early spermatids (Trostle-Weige et al, 1984). Despite that the other H3 variants are localized in all stages of germ cell types, these two H3 variants are thought to be involved in cellular proliferation and development by opening the chromatin structure as we recently reported (Ueda et al, 2017).…”
Section: Introductionmentioning
confidence: 71%
“…4), indicating that decreased expression of H3.5 per se may be involved in the deterioration of cellular function. Recently, we showed that the function of H3t is essential for the initial step of spermatogenesis and is required for spermatogonia (i.e., spermatogenic stem cells) to enter differentiation (Ueda et al, 2017). Based on the microscopic appearance of the chromosomal material, the primary spermatocyte stage was subdivided into preleptotene, leptotene, zygonema, pachynema, diplonema, and diakinesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During spermatogonia differentiation, H3t replaces canonical H3 proteins, thus forming a more open chromatin structure. H3t (H3T) containing nucleosomes are required for spermatogonial differentiation, and ensure entry into meiosis, as H3t gene deficiency leads to male infertility due to the failure of germ cell differentiation from spermatogonia to spermatocytes (Ueda et al 2017). CENPA is another histone H3 variant that is specifically localized at the centromeres and modulates their behavior (Niikura et al 2015).…”
Section: Histone H3 Variants In Meiosismentioning
confidence: 99%